Weighted BMO Estimates for Toeplitz Operators on Weighted Lebesgue Spaces. (16th June 2015) - Lin, Yan; Zhang, Mengmeng
Abstract : The authors establish the weighted BMO estimates for a class of Toeplitz operators related to strongly singular Calderón-Zygmund operators on weighted Lebesgue spaces. Moreover, the corresponding result for the Toeplitz operators related to classical Calderón-Zygmund operators can be deduced.